Resonant driving of magnetization precession in a ferromagnetic layer by coherent monochromatic phonons - Jäger, J.V.; Scherbakov, A.V.; Glavin, B.A.; Salasyuk, A.S.; Campion, R.P.; Rushforth, A.W.; Yakovlev, D.R.; Akimov, Andrey V.; Bayer, M. (American Physical Society, 2015)
We realize resonant driving of the magnetization precession by monochromatic phonons in a thin ferromagnetic layer embedded into a phononic Fabry-Pérot resonator. A femtosecond laser pulse excites resonant phonon modes of the structure in the 10−40 GHz frequency range. By applying an external magnetic field, we tune the precession frequency relative to the frequency of the phonons localized in the cavity and observe an enormous increase in the amplitude of the magnetization precession when the frequencies of free magnetization precession and phonons localized in the cavity are equal.